Heparin binding proteins in seminal plasma of breeding buffalo bulls and their relation with semen freezability and in vivo fertility - SINGH, A K; BRAR, P S; CHEEMA, RANJNA S (The Indian Journal of Animal Sciences, 2020)
The present study was conducted to determine the concentrations of heparin binding proteins (HBP) in seminal fluid of breeding buffalo bulls and establish their relationship with frozen-thawed semen characteristics and fertility. Both fresh and frozen semen were collected from same ejaculate of 30 breeding buffalo bulls. Based on HBP concentrations in seminal plasma obtained from affinity chromatography, all the bulls were divided into 2 groups, viz. high fertility bulls (HFB, ≥ 6.5 mg/ml; n=15) and low fertility bulls (LFB, < 6.5 mg/ml; n=15) for further comparisons. The frozen-thawed semen of same ejaculate was evaluated for per cent CASA-based sperm kinetics, viability, Hypo-osmotic swelling test (HOST), acrosome integrity, in vitro acrosome reaction and first service conception rate (FSCR). The overall HBP concentrations were significantly higher in seminal plasma (7.31±0.14 vs 5.33±0.19 mg/ml) and fresh (0.66±0.03 vs 0.59±0.02 mg/109 sperms) sperm extracts of HFB than LFB. The frozen-thawed semen characteristics, viz. total motility, per cent acrosome reaction and FSCR were also significantly higher in bulls with high fertility than in lower ones. No significant difference was observed in sperm viability, HOST and acrosome integrity in the 2 groups of bulls. Total 12 HBP bands in range of 11 to 135 kDa were recorded on SDS-PAGE. Higher levels of HBP in seminal plasma of HFB might be responsible for their better semen quality and fertility.